Design and development of kenaf harvesting machine - Ghahraei, Omid (2011)
Kenaf whole-stem having long bast fibres is more suitable for industries to produce textile and bio-composite panels. Current modified harvesters (sugarcane harvesters, forage harvesters, choppers, reaper binders, mower conditioners, pedestrian harvesters) normally chop the kenaf stems to small segments and/or crash the fibres or unable to cut the thick stems. So, a kenaf harvesting machine is required to cut the thick intact whole-stems having high capacity and satisfactory cutting quality with no damage on the bast fibres. Currently manual whole-stem harvesting which is a labour-intensive, time-consuming, and less profitable process, is being practiced in Malaysia. In this study, a new pull-type four-row whole-stem kenaf harvesting machine with a rotary impact cutting system was designed, developed and evaluated. The machine cutting system design was based on effective cutting knife edge angle (ANE) and cutting rotational speed. In this research, specific cutting force (SCF) and specif cutting energy (SCE) were measured by considering knife edge angle (ANE), shear angle (SA), knife approach angle (ANA), knife rake angle (ANR), and the cross‐sectional area of plant stems. In addition, an experimental impact cutting machine was manufactured and tested in the field. The rotational speed obtained with this machine had the lowest cutting torque. Kenaf stems of the V36 variety were used as the experimental material. An analysis of variance of the SCF and SCE values of the kenaf stems showed that the effects of all the above‐mentioned angles (considering a broad range) on SCF and SCE were significant. Moreover, the preferred values of ANE, SA, ANA, and ANR were 25°, 40°, 40°, and 40°,respectively, according to Duncan's multiple range test (DMRT). Based on the impact cutting test, the rotational cutting speed had a significant effect on the specific cutting torque. Increasing the rotational speed from 308 to 788 rpm decreased the cutting torque by 26.3%. The preferred rotational speed with a minimum cutting torque used in designing the cutting system was 712 rpm. The experimental impact cutting machine had an estimated effective field capacity of 0.56 ha/8 h day. The average moisture content of cut samples from the lower area of the stems was 70.78% (dry basis). The harvesting machine operated best at the field speeds of 3-6 km/h resulted from the cutting quality tests and recommended by DMRT. In preliminary field tests, the average values of the effective filed capacity (EFC), field efficiency (FE), and material capacity (MC) of the machine were found to be 1.68 ha/8 h day, 70.6%, and 114.8 t/8 h day for single-row harvesting (with 75 cm row spacing and about 20 stems/m of row) and 3.37 ha/8 h day, 74%, and 241.9 t/8 h day for 2-row harvesting (with 75 cm row spacing and about 20 stems/m of row), respectively at recommended speeds of 3-6 km/h. The average expected values of EFC, FE, and MC of the machine for 4-row harvesting (with 30 cm row spacing and 10 stems/m of row) were foreseen to be 2.92 ha/8 h day, 77%, and 249 t/8 h day, respectively at recommended speeds of 3-6 km/h in standard field conditions (planted by an accurate planter, proper watering and fertilization, and with no weed or grass). Maximum height, average diameter, average cutting height, and average moisture content of the kenaf stems at the harvesting time were measured as 3.10 m, 21.8 mm,20 cm, and 71.8% (dry basis), respectively. The highest recommended machine effective field capacity evaluated in this study was capable of replacing up to 370 persons per day when harvesting by traditional hand methods. Based on cost analysis results, the total manual harvesting operation cost was 32 times more than the total mechanical harvesting operation cost for harvesting 1,500 hectares of Malaysia kenaf fields for fibre production for one time plantation a year in 2010.